The Effect of Profitability, Company Activities, Liquidity and Asset Structure on Capital Structure in Consumer Goods Companies Listed on the Indonesia Stock Exchange 2017-2019 Period - Ferdinand Napitupulu; Manwardeep Kaur; Yusnito Sari; Leisa Febriani Sinaga (Enrichment : Journal of Management, 2021)
This study aims to determine the effect of profitability, company activity, liquidity, and asset structure on the capital structure of consumer goods companies listed on the IDX. The sample used in the study was 32 companies listed on the IDX for the 2017-2019 period. The independent variables in this study are profitability, company activity, liquidity, and asset structure. Meanwhile, the dependent variable is capital structure. The approach method used in this study is quantitative method. Judging from the results of this study that partially profitability has no and insignificant effect on capital structure, while company activities partially have a positive and significant effect on capital structure. and liquidity partially has a negative and significant effect on the capital structure, while the asset structure partially has no and insignificant effect on the capital structure. Simultaneously, profitability, company activity, liquidity, and asset structure have a significant and significant effect on capital structure.Based on the research results prove the value of the adjusted r squre () equal to 0.278 or 27.8%. This means that all independent variables are influenced by a number of 27.8% while 72.5% of the excess is influenced by variables outside the research.